The Irish revival : a complex vision - Valente, Joseph; Howes, Marjorie Elizabeth (Irish studies., 2023)
"In a series of essays by prominent Irish studies scholars, The Irish Revival: A Complex Vision deploys Complexity Theory to re-imagine the signature literary and cultural movement of modern Ireland as a unified structure of discrete projects, autonomously pursued"--